2020
DOI: 10.5276/jswtm/2020.77
|View full text |Cite
|
Sign up to set email alerts
|

Household Solid Waste Management in Monrovia, Liberia: Influencing Factors, Characteristics, and Management Solutions

Abstract: The ineffective management of household solid waste (HSW) in most developing cities in Africa including Monrovia has become a major issue threatening the environment and public health. In response to these waste challenges, developed countries have embarked upon major environmental reforms, and have made advances in best practices and sustainable management of their Municipal Solid Waste (MSW). However, in most developing countries like Liberia, such environmental reforms have not been initiated and therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Similarly, a study conducted by UNEP [23] found that waste is sub-divided into categories: organic (food scraps, papers cardboard, wood): inorganic waste (plastics, cans, bottles), and electronic waste (metals). Also, a recent study on the influencing factors of increased household waste generation conducted by [16] The results showed the composition of waste by households of different income groups. The study results further showed that waste generated by these diverse income groups varied from one household to another, as shown in Fig.…”
Section: Characteristics and Composition Of Waste In Liberiamentioning
confidence: 97%
See 4 more Smart Citations
“…Similarly, a study conducted by UNEP [23] found that waste is sub-divided into categories: organic (food scraps, papers cardboard, wood): inorganic waste (plastics, cans, bottles), and electronic waste (metals). Also, a recent study on the influencing factors of increased household waste generation conducted by [16] The results showed the composition of waste by households of different income groups. The study results further showed that waste generated by these diverse income groups varied from one household to another, as shown in Fig.…”
Section: Characteristics and Composition Of Waste In Liberiamentioning
confidence: 97%
“…However, most developing countries including Liberia are falling behind because of the lack of resources, lack of technical and technological skills, weak legislation, etc. [16,31,33].…”
Section: Regulatory and Legislative Frameworkmentioning
confidence: 99%
See 3 more Smart Citations